A Great Exhibition of Printing: The Illustrated London News Supplement Sheet (1851) - Paul Fyfe (Cahiers Victoriens et Edouardiens)
The Illustrated London News offered extensive coverage of the Great Exhibition of 1851 and even exhibited one of its own printing machines in the ‘Machines in Motion’ display. The ILN’s printing press helped supply its illustrated supplements for the Great Exhibition and stoked visitors’ curiosity about the steam-driven press at the show: an Applegath four-feeder printing from a revolving vertical type drum. Notably, this machine was printing mostly text-based pages on a single side. The periodical’s signature illustrations had to be printed on a different press at the ILN’s offices in the Strand. This article recreates the twinned origins of a single leaf of paper from the ILN’s Great Exhibition supplement from 31 May 1851 as evidence of the changing ontology of industrially printed things at mid-century. The sheet demonstrates the technological evolution of illustrated periodicals as well as their hybrid conceptual status, blending text and image in a genre that claimed the immediacy of news. Ultimately, the ILN celebrated its industrial processes as a guarantee of visual fidelity, offering its illustrations not only for what they visually represent but also as material artefacts of its own production.